Culture as Power: Buddhist Heritage and the Indo-Japanese Dialogue - Bhalla, Madhu (London: Routledge, Taylor & Francis Group, 2021)
This book presents new studies on intellectual and cultural interactions in the context of Buddhist heritage and Indo-Japanese dialogue in the late 19th and early 20th centuries on art, religion, and cultural politics. By revisiting Buddhist connections between India and Japan, it examines the pathways of communication on common aesthetic and religious heritage that emerged in the backdrop of colonial experiences and the rise of Asian nationalisms. The volume discusses themes such as Asian arts and crafts under colonialism, formation of East Asian art collections, development of Buddhist art history in Japan, Japanese encounters with Ajanta, India in the history of the Shinto tradition, Japan in India's xenology, and Buddhism and world peace, and suggests paradigms of reconnecting cultural heritage within a global platform. With essays from experts across the world, this book will be an essential read for scholars and researchers of history, art history, ancient Indian history, colonial history, heritage and cultural studies, South Asian and East Asian history, visual and media studies, Asian studies, international relations and foreign policy, and the history of globalization
Keywords: Buddhism and culture -- Congresses; Art and religion -- Congresses. -- East Asia; Religion and politics -- Congresses. -- East Asia; Buddhist art -- Congresses. -- Japan -- India